Pengaruh Pelayanan dan Fasilitas Poli Gigi terhadap Kesiapan Tempur Prajurit Pasmar 2 - Nugroho, Achmad; Herman, Juli; Ilmi, Muhammad Irfan (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The Marine Corps is tasked with developing the strength and operational readiness of its units and fostering maritime potential into a force for sea defense and security under the Chief of Naval Staff's responsibility. This study aims to analyze the impact of service quality and dental clinic facilities at on the combat readiness of Pasmar 2 personnel. Using a quantitative approach with a descriptive method, the research involved 98 respondents selected from a total population of 7,461 personnel. Data was collected through questionnaires designed to assess respondents' perceptions of the service quality and dental clinic facilities and their impact on combat readiness. The independent variables include service quality and the completeness of dental clinic facilities, while the dependent variable is the combat readiness of personnel. Data analysis was conducted using SPSS version 27, covering validity tests, reliability tests, and regression analysis. The results indicate that both service quality and dental clinic facilities significantly affect personnel's combat readiness, both individually (partial) and collectively (simultaneous). Key influencing factors include the availability of specialist medical staff, adequate medical equipment, and the efficiency of dental health care processes.